They called her Mrs. Doc - Oke, Janette, 1935- (Minneapolis, Minn. : Bethany House, 1992)
Cassandra is unprepared for the lack of culture and manners in the West.
820
Accelerated Reader AR
Keywords: Historical fiction; Medical novels; Love stories; Historical fiction; Western stories; Christian fiction